Effects of dietary crude protein on antioxidant activity, immunocompetence and the structural properties of the rumen in tibetan sheep (Ovis aries), as determined by transcriptomic analysis - Zhenling Wu; Fengshuo Zhang; Quyangangmao Su; Qiurong Ji; Kaina Zhu; Tingli He; Xuan Chen; Yu Zhang; Jiacheng Gan; Wei Gao; Xianhua Zhang; Geerli Saren; et al. (Cogent Food & Agriculture)
The rumen is a balanced ecosystem that harbors a variety of microorganisms and plays a crucial role in the digestion and absorption of nutrients in ruminants. This study aimed to evaluate the effects of dietary crude protein on antioxidant activity, immunocompetence, and structural properties in the rumen of Tibetan sheep. 60 2-month-old male lambs with an average weight of 15.40 ± 0.81 Kg were randomly assigned to either a low-protein diet (10.20% of dry matter, LP group) or a high-protein diet (11.58% of dry matter, HP group). The experiment was conducted over 97 days, including a 7-day adaptation period to the diets. The results indicated that the high-protein diet significantly increased rumen weight, rumen volume, papilla length, papilla width, and muscle layer (p < 0.05). Compared to the 10.20% protein group, supplementation with 11.58% crude protein significantly increased the activities of total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) (p < 0.05). A total of 446 significant differentially expressed genes (DEGs) were identified in response to the high-protein diet (426 upregulated and 20 downregulated). Based on Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis, six signaling pathways related to nutrient metabolism, antioxidant activity, and immunity were identified. Protein-protein interaction (PPI) analysis identified genes involved in fatty acid biosynthesis (ACACB and ACSF3), nutrient metabolism (ATP1B1, SLC5A1, IDH2, ATP1A2, NT5E, and NNT), and muscle development (MYH11, KCNMA1, and MYL9). In conclusion, an 11.58% crude protein diet enhanced papillary development and antioxidant activity in Tibetan sheep, likely by modulating the expression of functional genes.